Konzept für ein hierarchisches autonomes Verkehrsmanagement - Mertin, Sven

Online State Estimation for Microscopic Traffic Simulations using Multiple Data Sources* - Malena, Kevin; Link, Christopher; Mertin, Sven; Gausemeier, Sandra; Trächtler, Ansgar (VEHITS 2021 Proceedings of the 7th International Conference on Vehicle Technology and Intelligent Transport Systems)
The online fitting of a microscopic traffic simulation model to reconstruct the current state of a real traffic area can be challenging depending on the provided data. This paper presents a novel method based on limited data from sensors positioned at specific locations and guarantees a general accordance of reality and simulation in terms of multimodal road traffic counts and vehicle speeds. In these considerations, the actual purpose of research is of particular importance. Here, the research aims at improving the traffic flow by controlling the Traffic Light Systems (TLS) of the examined area which is why the current traffic state and the route choices of individual road users are the matter of interest. An integer optimization problem is derived to fit the current simulation to the latest field measurements. The concept can be transferred to any road traffic network and results in an observation of the current multimodal traffic state matching at the given sensor position. First case studies show promosing results in terms of deviations between reality and simulation.
Keywords: Microscopic Traffic Simulation; Online State Estimation; Mixed Road Users; Sensor Fusion; Integer Programming; Route Choice; Vehicle2Infrastructure

Validation of an Online State Estimation Concept for Microscopic Traffic Simulations◆ - Malena, Kevin; Link, Christopher; Mertin, Sven; Gausemeier, Sandra; Trächtler, Ansgar (2021 IEEE Transportation Electrification Conference & Expo (ITEC))
This paper deals with a novel method for the online fitting of a microscopic traffic simulation model to the current state of a real world traffic area. The traffic state estimation is based on limited data of different measurement sources and guarantees general accordance of reality and simulation in terms of multimodal road traffic counts and vehicle speeds. The research is embedded in the challenge of improving the traffic by controlling the traffic light systems (TLS) of the examined area. Therefore, the current traffic state and the predicted route choices of individual road users are the matter of interest. The concept is generally transferable to any road traffic system. To give an impression of the accuracy and potential of the approach, the validation and first application results are presented.

Design and Evaluation of a Novel Filter-Based Motion Cueing Strategy for a Hybrid Kinematics Driving Simulator with 5 Degrees of Freedom - Biemelt, Patrick; Mertin, Sven; Rüddenklau, Nico; Gausemeier, Sandra; Trächtler, Ansgar (Proceedings of the Driving Simulation Conference Europe VR)

Macroscopic Traffic Flow Control using Consensus Algorithms - Mertin, Sven; Malena, Kevin; Link, Christopher; Gausemeier, Sandra; Trächtler, Ansgar (The 23rd IEEE International Conference on Intelligent Transportation Systems)

Objective Evaluation of a Novel Filter-Based Motion Cueing Algorithm in Comparison to Optimization-Based Control in Interactive Driving Simulation - Biemelt, Patrick; Mertin, Sven; Rüddenklau, Nico; Gausemeier, Sandra; Trächtler, Ansgar (Proceedings of the International Conference on Advances in System Simulation (SIMUL))

Simulation-Based Lighting Function Development of High-Definition Headlamps - Rüddenklau, Nico; Biemelt, Patrick; Mertin, Sven; Gausemeier, Sandra; Trächtler, Ansgar (13th International Symposium on Automotive Lighting (ISAL))

Proof-of-Concept einer komplexen Co-Simulationsumgebung für einen Fahrsimulator zur Untersuchung von Car2X-Kommunikations-Szenarien - Mertin, Sven; Buse, Dominik; Franke, Mario; Trächtler, Ansgar; Gausemeier, Sandra; Dressler, Falko (VDI/VDE AUTOREG 2019)

Real-Time Lighting of High-Definition Headlamps for Night Driving Simulation - Rüddenklau, Nico; Biemelt, Patrick; Mertin, Sven; Gausemeier, Sandra; Trächtler, Ansgar (IARIA SysMea)

Shader-Based Realtime Simulation of High-Definition Automotive Headlamps - Rüddenklau, Nico; Biemelt, Patrick; Henning, Sven; Gausemeier, Sandra; Trächtler, Ansgar (SIMUL 2018, The Tenth International Conference on Advances in System Simulation)

A Simulation Framework for Testing a Conceptual Hierarchical Autonomous Traffic Management System including an Intelligent External Traffic Simulation - Henning, Sven; Biemelt, Patrick; Rüddenklau, Nico; Gausemeier, Sandra; Trächtler, Ansgar (Proceedings of the DSC 2018 Europe VR: New trends in Human in the Loop simulation and testing. Driving simulation and VR)

A Model Predictive Motion Cueing Strategy for a 5-Degree-of-Freedom Driving Simulator with Hybrid Kinematics - Biemelt, Patrick; Henning, Sven; Rüddenklau, Nico; Gausemeier, Sandra; Trächtler, Ansgar (Proceedings of the Driving Simulation Conference Europe VR (DSC))

Modellbasierte Untersuchung der Zuverlässigkeit algorithmisch bestimmter kritischer Stellen in Straßennetzwerken - Henning, Sven; Biemelt, Patrick; Abdelgawad, Kareem; Gausemeier, Sandra; Trächtler, Ansgar (VDI/VDE (AUTOREG 2017))

Networked Driving Simulation for Future Autonomous and Cooperative Vehicle Systems - Abdelgawad, Kareem; Henning, Sven; Biemelt, Patrick; Gausemeier, Sandra; Trächtler, Ansgar (VDI/VDE (AUTOREG 2017))

Methodology for Determining Critical Locations in Road Networks based on Graph Theory - Henning, Sven; Biemelt, Patrick; Abdelgawad, Kareem; Gausemeier, Sandra; Trächtler, Ansgar (IFAC World Congress 2017)

Advanced Traffic Simulation Framework for Networked Driving Simulators - Abdelgawad, Kareem; Henning, Sven; Biemelt, Patrick; Gausemeier, Sandra; Trächtler, Ansgar (AAC2016 (IFAC), 8th IFAC Symposium on Advances in Automotive Control (AAC 2016))